한국 광역지방자치단체 공무직 임금의 결정요인 연구 : 공무원 규모, 지역의 소득수준, 지역 재정수준을 중심으로 - 서인석; Inseok Seo; 이제선; Jesun Lee; 정원희; Wonhee Jung (한국행정연구, 2024)
공무 수행의 관점에서 공무원과 다르지 않은 ‘공무직’ 임금결정이 공무원과 다르다는 점을 인식하고, 어떤 맥락에서 결정되는 것인지를 실증적으로 확인해보고자 하였다. 분석결과를 통해, 몇 가지 의미를 확인할 수 있었다. 우선, 공무원 규모와 관련된 가설은 모두 통계적으로 유의미하였다는 점이다. 공무직 인원 규모와 인건비 비율, 그리고 일반공무원 인원 규모와 인건비 비율 등은 모두 의미있는 가설관계를 확인하였다. 다만, 상대적 비교가 가능한 일반공무원과 공무직의 관계임을 감안해 향후 지속적으로 검증될 필요가 있다. 둘째, 한국과 같은 지역 간 거리가 짧은 국가에서조차 지역의 물가 수준이 상이할 수 있고, 그 격차가 임금격차의 주요 원인이 될 수 있다는 점을 확인하였다는 점이다. 셋째, 지방재정 수준에서 GRDP는 중요한 인자로 확인되었다. 물론, 상식수준에서도 GRDP의 증대는 근로자 전반의 임금상승을 견인할 수 있다. 단체협상의 성격을 지니는 공무직 역시 예외가 되지 않을 것이다. 본 연구 결과는 이를 잘 드러내고 있다. 넷째, 이론적 시사점으로써 한국적 맥락의 특성을 지니는 공무직 현상을 규명하고자 하였다는 점이다. From the perspective of public service duties, this study aims to empirically investigate how wage decisions for public employees, referred to as gongmujik, differ from those of civil servants, despite their similar nature in terms of public duties. Through the analysis, several significant findings have emerged. First, hypotheses related to the size of the civil servant workforce were statistically significant. Both the size of the gongmujik workforce and the ratio of labor costs, as well as the size of the general civil servant workforce and their labor cost ratio, were found to have meaningful relationships. However, given the relative comparability between general civil servants and gongmujik, further validation of these relationships is necessary. Second, even in a country like Korea, where distances between regions are relatively short, the cost of living can vary by region, and this disparity can be a key factor contributing to wage differences. Third, at the local financial level, GRDP was identified as an important factor. The increase in GRDP, even at a common-sense level, can drive wage growth for workers in general, and public employees, who are subject to collective bargaining, are no exception. The findings of this study clearly demonstrate this. Fourth, as a theoretical implication, this study seeks to identify the unique characteristics of gongmujik in the context of the Korean environment.